Novel Treatments in Refractory Recurrent Pericarditis - Emilia Lazarou; Christos Koutsianas; Panayotis K. Vlachakis; Panagiotis Theofilis; Dimitrios Vassilopoulos; Costas Tsioufis; George Lazaros; Dimitris Tousoulis (MDPI AG, 2024)
Refractory recurrent pericarditis is a troublesome condition that severely impairs the quality of life of affected patients and significantly increases healthcare spending. Until recently, therapeutic options included only a few medications and most of the patients resorted to chronic glucocorticoid treatment with steroid dependence. In the most recent decade, the introduction of interleukin-1 blockers in clinical practice has revolutionized the treatment of glucocorticoid-dependent and colchicine-resistant recurrent pericarditis due to their excellent efficacy and good safety profile. The rationale for the introduction of this class of medications in clinical practice is the autoinflammatory nature of recurrent pericarditis in a substantial rate of cases, with interleukin-1 being the main pro-inflammatory cytokine involved in this context. This review aims to discuss the contemporary available evidence from original research and real-world data on interleukin-1 blocker use in refractory recurrent pericarditis, in terms of indications, mechanism of action, efficacy, side effects, and recommended treatment protocols. Moreover, novel treatment proposals, such as hydroxychloroquine, beta blockers, and cannabidiol, which showed encouraging preliminary results, are addressed. Finally, gaps in knowledge, unmet needs, and future perspectives related to recurrent pericarditis are thoroughly discussed.